2011
DOI: 10.1123/jsm.25.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Benefits of Mega Events: A Myth or a Reality? A Longitudinal Study on the Olympic Games

Abstract: This study concerns research related to mega events, such as the Olympic Games, to determine whether the economic impact of the Olympic Games on the host countries is significant. This study uses two methods, panel data analysis and event study, to test hypotheses based on the data from 15 countries that have hosted 24 summer and winter Olympic Games. The results indicate that the economic impact of the Olympic Games on the host countries is only significant in terms of certain parameters (i.e., gross domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 26 publications
0
33
0
4
Order By: Relevance
“…More and more literature has focussed on actual impacts, particularly the economic impacts (Dobson, 2000;Dobson & Gratton, 1995;Gratton et al, 2005;Gratton & Preuss, 2008;Hall, 2006;Solberg & Preuss, 2007;Roche, 1992;Tien, Lo, & Lin, 2011) given the view that numerous visitors travel and spend significant sums during their stay.…”
Section: Literature Reviewmentioning
confidence: 98%
“…More and more literature has focussed on actual impacts, particularly the economic impacts (Dobson, 2000;Dobson & Gratton, 1995;Gratton et al, 2005;Gratton & Preuss, 2008;Hall, 2006;Solberg & Preuss, 2007;Roche, 1992;Tien, Lo, & Lin, 2011) given the view that numerous visitors travel and spend significant sums during their stay.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This spectacle is also valued by nations, since it provides them with a unique opportunity to attract more widespread recognition (Xu, 2006), test their elite sport policies and gain a competitive advantage over other countries (De Bosscher, Shilbury, Theeboom, Van Hoecke, & De Knop, 2011). For the host city of an Olympic Games, the mega-event presents them with the chance to showcase themselves, their facilities and their planning capabilities to a global audience, as well as the prospect of making investments in infrastructure, generating income and employment opportunities, attracting tourists and increasing national pride (Gibson, Qi, & Zhang, 2008;Green & Houlihan, 2005;Kasimati, 2003;Rose & Spiegel, 2011;Tien, Lo, & Lin, 2011). Notwithstanding these benefits, research has also found that a spectacle of this magnitude can, perhaps inevitably, create many issues for those managing and leading Olympic venues, programmes and teams.…”
mentioning
confidence: 98%
“…A number of urban developmental modes have been attributed to the building and development for Olympics. The large scale 'spectacle' of opening ceremonies (Broudehoux, 2010;Tien, Lo, & Ze, 2011;Müller, 2011) are often seen as complex megaprojects, with the Berlin 1936 Olympics often being cited as the first case of upscaling the Olympics to a mega-event, which generated a desire to present these events in a new grand schema.…”
Section: Disciplining Megaprojectsmentioning
confidence: 99%